Keterbacaan Hasil Penerjemahan Kitab Fathu al-Qarīb ke dalam Bahasa Indonesia oleh Santri - Zahidah, Syifa Nadiatuz (Jurnal Penerjemahan, 2021)
In translation, providing comprehensible reading is one of its objectives. In the same vein, this study aims to determine the translation readibility of the Fathu Al Qarīb book. To this end, the research uses a qualitative approach with descriptive analysis techniques to describe the quality of readability from the translation of the heritage book. The text used in this study is the text of the book Fathu Al Qarīb in the form of book introduction and a book title. The results of this study reveal that the degree of legibility of the translation of the book of Fathu Al Qarīb, based on the reader's response with the Cloze Test, is in the instructional category or is at a moderate degree. Meanwhile, by using the Gunning Fog Index, the first and second texts are at a low level and the third text is at a moderate level. Keywords: ngalogat method, translation techniques, translation quality